Expanding long-term care insurance could reduce the gender care gap in Germany - Johannes Geyer; Peter Haan; Mia Teschner (DIW Weekly Report, 2024)
In many European countries, men and women differ significantly in the amount of informal care work they provide for relatives, with women acting as caregivers far more frequently than men. This difference, known as the gender care gap, varies considerably between European countries, with Germany somewhere in the middle of the distribution. This Weekly Report analyzes the institutional, societal, and labor market factors that are related to the gender care gap across European countries. The results show that the gap is smaller in countries that spend more on the formal care system. In addition, they show that the gender care gap tends to be larger in countries that exhibit high gender inequality and high inequality in labor market participation between men and women. Thus, the results emphasize that the gender pay gap correlates with government investments in health care, the care system, and the labor market structure. To reduce the gender care gap, expenditure on formal care should be increased to relieve informal caregivers and improve the quality of care in professional facilities. At the same time, policymakers should use tax and family policy incentives to increase women's workforce participation so that paid work and care work are more evenly distributed.
Keywords: D13; J16; J22; 330; Long-term Care; Gender Care Gap; Gender inequality; SHARE